Small scale PV monitoring system software design - Anwari, Makbul; Murtadza, Md Dom; Muhammad Ikram, Mohd Rashid (Elsevier Ltd, 2011)
Photovoltaic system installation is a costly venture. Due to this, valuable information from the system such as the efficiency, performance and energy produced are mostly required by the user. Thus, developing a small scale photovoltaic monitoring system give the user vital information on the return of investment of the installation. In this design, a small scale photovoltaic monitoring system using PIC16F877a microcontroller and LabVIEW is designed and developed. PIC microcontroller is chosen for the cost effectiveness of it. Research is done on how to monitor the data using the analog to digital conversion of the microcontroller and also data storage and transmission using LabVIEW. The developed system is able to simulate and monitor the photovoltaic array voltage and photovoltaic array ampere drawn from the system. Additional data from the environment such as ambient temperature and solar irradiance data is also simulated and monitored. The monitoring software is developed using LabVIEW.